A la conquista de la tierra y del cielo: Rascacielos y poder tecno-económico - Roche Cárcel, Juan A. (Política y Sociedad, 2008)
Along this work we have analyzed the way skyscrapers build a representation of the reality and of the economical world, how the will of power –particularly economic– is expressed and which is the nature of that power. And we conclude that the will of power reiterated by skyscrapers can be seen as uncontrollable, unsatisfied and insatiable of life and deeply irrational, so we can say that the Schopenhauer, Nietzsche and Freud programs have been completed as far as for them, power means the absolute and unlimited, irrational and blind will to live. But, at the same time, skyscrapers compliment the weberian program because they search for legitimacy and exemplify a certain visible configuration of power, individual and collective, personal and impersonal. In a few words, although skyscrapers from an horizontal point of view look close to the city and earth, vertically seem move away form earth which denotes, finally that they pretend not only triumph over earth but over the sky.
Keywords: Sociology of Art; Skyscrapers; Power; Architecture